The role of oxidized lipid species in insulin resistance and NASH in children - Santoro, Nicola; Feldstein, Ariel E. (Frontiers in Endocrinology, 2022)
During the last two decades nonalcoholic fatty liver disease (NAFLD) has emerged as the most common hepatic disease in Pediatrics, mainly owing to the raining prevalence of Pediatric obesity. Epidemiological studies have shown that the progressive increase in NAFLD prevalence is associated not only with obesity, but also with changes in dietary habits experienced by all ages groups characterized by the increased intake of added sugars and certain fatty acids. In this review article we will focus on the effect of oxidized fatty acids deriving from linoleic acid (LA) and arachidonic acids (AA) on the pathogenesis and progression of NAFLD in youth.